On a new space of defined by using Orlicz functions - Bektas, Cigdem A.; Ercan, Sinan; Zeren, Swan (Amer Inst Physics, 2017)
In this paper we introduce a paranormed sequence space BV sigma (M, p, q, u) defined by a sequence of Orlicz functions. We examine some properties of this space.
11th International Conference on Mathematical Problems in Engineering, Aerospace and Sciences (ICNPAA) -- JUL 04-08, 2016 -- Univ La Rochelle, La Rochelle, FRANCE